Problematika Poligami Di Indonesia Analisis Normatif dan Sosiologis dalam Hukum Keluarga Islam - Fahrun Dama; fahrun21 (HOKI : Journal of Islamic Family Law, 2025)
Polygamy is a practice permitted under Islamic law with strict conditions, but its implementation in Indonesia often sparks debate both normatively and sociologically. Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI) have imposed more restrictive regulations on the practice of polygamy to ensure the protection of women's and children's rights. This article aims to analyze the issues surrounding polygamy in Indonesia through a normative approach to Islamic legal texts and regulations, as well as a sociological approach to the evolving social reality. The findings of the study indicate that the practice of polygamy is often The study findings indicate that the practice of polygamy is often influenced by economic, social, and cultural factors, while religious courts serve as a legal filter to ensure the fulfillment of the principle of justice. This analysis emphasizes the importance of reinterpreting the maqāṣid al-syarī‘ah in the practice of polygamy to remain relevant to the values of justice, gender equality, and the protection of human rights.